Evolutionary game theory - Alexander, Jason 1972- (Cambridge University Press, 2023)
This publication covers the two main approaches to evolutionary game theory: the static analysis of evolutionary stability concepts, and the study of dynamical models, their convergence behaviour and rest points. It also explores the many fascinating, and complex, connections between the two approaches
Also issued in print: 2023. - Includes bibliographical references
Keywords: Game theory; Evolution / Mathematical models; Spieltheorie